2000
DOI: 10.1677/joe.0.1660265
|View full text |Cite
|
Sign up to set email alerts
|

Primary cultured hepatocytes of the bony fish, Oreochromis mossambicus, the tilapia: a valid tool for physiological studies on IGF-I expression in liver

Abstract: In spite of the importance of IGF-I for growth and development, knowledge about regulation of its production in submammalian species is rather limited. In order to create a tool for investigation of direct regulatory effects on the expression of IGF-I in bony fish liver, a primary cell culture of hepatocytes from Oreochromis mossambicus, the tilapia, was established. The cells were viable for up to 3 days and IGF-I mRNA synthesis was detected by northern blot and semiquantitative reverse transcriptase (RT)-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 44 publications
6
25
0
Order By: Relevance
“…Both igf1 and igf2 mRNA levels were stimulated by GH in tilapia primary hepatocytes, as has been found in previous in vitro studies in teleost fishes and elasmobranches (Shamblott et al 1995, Schmid et al 2000, Pierce et al 2004, Leung et al 2008, Moriyama et al 2008a. Recent in vivo studies have shown that GH treatment increases liver igf2 mRNA levels in a wide variety of fish species (see Introduction for citations), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both igf1 and igf2 mRNA levels were stimulated by GH in tilapia primary hepatocytes, as has been found in previous in vitro studies in teleost fishes and elasmobranches (Shamblott et al 1995, Schmid et al 2000, Pierce et al 2004, Leung et al 2008, Moriyama et al 2008a. Recent in vivo studies have shown that GH treatment increases liver igf2 mRNA levels in a wide variety of fish species (see Introduction for citations), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…5!10 K9 M) to the medium increased mRNA levels of both igfs versus time-matched controls. Basal and GH-stimulated igf1 decreased with time in previous studies with primary tilapia and salmon hepatocytes (Schmid et al 2000, Pierce et al 2004. Based on the results for these and other transcripts, an incubation time of 6 h was selected, giving a total culture age of 10 h.…”
Section: Resultsmentioning
confidence: 99%
“…GH consistently stimulated IGF-I mRNA expression in salmon hepatocytes, as in previous studies using salmonid hepatocyte culture , Shamblott et al 1995, Pierce et al 2004a) and tilapia hepatocyte culture (Schmid et al 2000). Consistent stimulation of IGF-I mRNA expression by GH in fish hepatocyte culture confirms that this functional relationship in the GH/IGF axis is conserved in fishes (Nicoll et al 1999, PerezSanchez & Le Bail 1999, Mommsen 2001).…”
Section: Discussionsupporting
confidence: 84%
“…Model systems, devoid of the existing endogenous influences in the organism, are suitable tools for studying physiological mechanisms in vitro for the first testing period [1]. They are therefore useful in vitro systems to examine adaptive mechanisms of cardiomyocytes to varied environmental influences.…”
Section: Introductionmentioning
confidence: 99%